2021
DOI: 10.1038/s41598-021-83334-6
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetic vascular hyperpermeability: optical coherence tomography angiography and functional loss assessments of relationships among retinal vasculature changes

Abstract: Our study assessed the influence of vascular permeability on vascular flow density (FD)-correlated retinal sensitivity (RS) in DR. In this cross-sectional, prospective, consecutive study, RS in the extrafoveal macula of DR patient was measured by microperimetry. FD was measured in the total, superficial, and deep capillary plexus layers (TCP, SCP, and DCP) by optical coherence tomography angiography. All measurement points were classified into four categories according to intensity of fluorescein leakage and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…To date, it is unclear whether there is a correlation between OCT metrics and microperimetry outputs in patients with diabetic eye disease ( Sachdev et al, 2019 ); recent work identified a correlation between OCTA-assessed vessel density (but not FAZ area) and microperimetry-assessed retinal sensitivity in eyes with advanced DR, but not in eyes with lower grades of severity ( Levine et al, 2022 ) and in eyes with retinitis pigmentosa ( Hagag et al, 2019 ). By using microperimetry and OCTA quantitative flow density, Arima et al showed that vascular hyperpermeability may inhibit the retinal sensitivity reduction in the non-edematous ischemic diabetic retina ( Arima et al, 2021 ). These findings highlight the potential value of combining these innovative tools for a more comprehensive understanding of the functional and structural implications of diabetic eye diseases.…”
Section: Relating Optical Coherence Tomography Angiography Metrics To...mentioning
confidence: 99%
“…To date, it is unclear whether there is a correlation between OCT metrics and microperimetry outputs in patients with diabetic eye disease ( Sachdev et al, 2019 ); recent work identified a correlation between OCTA-assessed vessel density (but not FAZ area) and microperimetry-assessed retinal sensitivity in eyes with advanced DR, but not in eyes with lower grades of severity ( Levine et al, 2022 ) and in eyes with retinitis pigmentosa ( Hagag et al, 2019 ). By using microperimetry and OCTA quantitative flow density, Arima et al showed that vascular hyperpermeability may inhibit the retinal sensitivity reduction in the non-edematous ischemic diabetic retina ( Arima et al, 2021 ). These findings highlight the potential value of combining these innovative tools for a more comprehensive understanding of the functional and structural implications of diabetic eye diseases.…”
Section: Relating Optical Coherence Tomography Angiography Metrics To...mentioning
confidence: 99%